Peranan Pastoral Konseling Dalam Pendampingan Kepastian Keselamatan Pada Warga Lansia di GKPB Imanuel Tabanan - Kowal, Roike R; Wakkary, Adriaan MF; Wijaya, Ratri Kusuma; Latuheru, Anita Ivonne (STT Kingdom, 2024)
The aim of the research is formulated in the following statement: to find out the ways or methods of pastoral counseling in providing joy to the elderly, to find out how pastoral counseling assistance provides comfort to the elderly to get rid of feelings of unnecessaryness and loneliness, to find out how pastoral counseling assistance works. in generating a sense of certainty about where the elderly will go after death. The research method used by the author is a qualitative research method. The results of the study concluded that elderly people often feel lonely and empty because their children are far away because of work or are married. So ultimately the elderly can experience depression. Regarding spiritual activities, this elderly group may still be able to do them even though they are very limited, but their desire to be close to God is very strong. The spirituality of the congregation and through pastoral counseling services can be an alternative answer to determining the appropriate discipleship model in a church specifically for the elderly.